Hubungan Intensitas Pemanfaatan Perpustakaan Terhadap Hasil Belajar Mahasiswa: Study Kasus pada UPT Perpustakaan Universitas Muhammadiyah Bengkulu - Susanti, Meri (TIK ILMEU : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
Teaching and learning activities take place both in either a classroom with a lecturer or outside of classroom such as at home and library to achieving educational goals. In the process of teaching and learning in the campus lecturers are required to perform optimally the curriculum that has been set in the form of syllabus. One of the components contained in the syllabus is teaching methods as well as the means and resources of the lessons that will be given to the students, who have an important role in implementing the learning process to achieve the set goals. Library has an important role in supporting the learning materials required by students and support the smooth teaching and learning process so that the goals set can be achieved. The attainment of this goal for the personal development of students educates themselves on an ongoing basis to solve problems and enhance social attitudes. The existence of UPT Library at the University of Muhammadiyah Bengkulu is very important because teaching and learning activities are generally limited and incomplete and often is a new supporter for the development of student lessons. So clearly the essence of UPT UMB library is the center of learning resources and information sources. From the observation, many students of Muhammadiyah University of Bengkulu were still very rarely visit the library, and they had lack of interest in reading. Based on these problems, the writer was interested in raising the title "Intensity of Library Exposure to Students Learning Outcomes (Case Study of Muhammadiyah University of Bengkulu). The formulation of the problem was how the Intensity Relationship Utilization UPT Library University of Muhammadiyah Bengkulu and how the results of student learning University of Muhammadiyah Bengkulu. The purpose of this study to determine the relationship of Intensity Utilization of UPT Library University of Muhammadiyah Bengkulu and to know the results of student learning University of Muhammadiyah Bengkulu